The Role of Tumour Microenvironment in Cancer Progression and Therapeutic Resistance Mechanisms and Implications for Treatment Strategies - Nadeem, Habibah; Shahzad Virk, Muhammad Kashif; Abbas, Faizan; Nawaz, Zahra; Ahmad, Muhammad Waseel; Binyameen, Musab (Indus Journal of Bioscience Research, 2025)
This study explores the critical role of the tumor microenvironment (TME) in cancer progression and therapeutic resistance, aiming to provide insights into novel treatment strategies targeting the TME. Using a quantitative research design, both in vitro and in vivo experiments were conducted, coupled with clinical data analysis from 92 patients diagnosed with breast, colon, and lung cancer. The methodology involved collecting tumor tissue samples, patient clinical records, and analyzing immune cell infiltration, fibroblast activity, and ECM remodeling within the TME. Multivariate regression analysis, Kaplan-Meier survival analysis, and Chi-Square tests were employed to examine the relationship between TME characteristics and patient survival. The results revealed that high immune cell infiltration was significantly associated with improved survival, while extensive ECM remodeling was linked to poorer survival outcomes. Treatment strategies, particularly chemotherapy and immunotherapy, demonstrated substantial improvements in patient response, with immunotherapy showing the strongest correlation with survival. This research emphasizes the critical role of the tumor microenvironment (TME) in cancer progression and treatment resistance. Key TME components—immune cells, fibroblasts, and extracellular matrix (ECM) remodeling—significantly impact patient outcomes. Elevated immune infiltration improves survival, while excessive ECM remodeling predicts poor prognosis. Combining traditional therapies like chemotherapy with immunotherapy or TME-targeting drugs offers promising individualized approaches. Future research should focus on personalized strategies tailored to a patient’s TME profile, with real-time monitoring guiding adaptive treatments. Novel agents targeting fibroblasts or ECM and advancements like 3D organoids or PDX models will enhance therapeutic testing. Multidisciplinary efforts are vital to translate these insights into clinical success and to overcome therapy resistance through TME-targeted interventions.